Hydroxysafflor yellow A for ischemic heart diseases: a systematic review and meta-analysis of animal experiments - Mao, Tianshi; Jiang, Kaixin; Pang, Yanting; Pan, Yi; Jia, Wenhao; Gao, Qun; Lin, Qian (Frontiers in Pharmacology, 2025)
BackgroundHydroxysafflor yellow A (HSYA) possesses a variety of pharmacological activities which has been demonstrated to be effective against ischemic heart disease (IHD). This study aimed to comprehensively examine the efficacy and summarize the potential mechanisms of HSYA against IHD in animal models.MethodsWe conducted electronic searches for preclinical studies on PubMed, Embase, Web of Science, Cochrane Library, CNKI, SinoMed, Wanfang, and Chinese VIP databases from inception to 31 January 2024. The CAMARADES checklist was chosen to assess the quality of evidence. STATA 14.0 software was utilized to analyze the data. The underlying mechanisms were categorized and summarized.ResultsTwenty-eight studies involving 686 rodents were included and the mean score of methodology quality was 5.04 (range from 4 to 7). Meta-analysis observed that HSYA could decrease myocardial infarction size (SMD: −2.82, 95%CI: −3.56 to −2.08, p < 0.001) and reduce the levels of biomarkers of myocardial injury including cTnI (SMD: −3.82, 95%CI: −5.20 to −2.44, p < 0.001) and CK-MB (SMD: −2.74, 95%CI: −3.58 to −1.91, p < 0.001). HSYA displayed an improvement in cardiac function indicators including LVEF, LVSP, +dp/dt max and -dp/dt max. Furthermore, HSYA was able to reduce the levels of MDA, TNF-α and IL-6, while increasing SOD and NO levels. Mechanistically, the protective effect of HSYA in alleviating myocardial injury after ischemia may be associated with NLRP3 inflammasome, Bcl-2, Bax, caspase-3, eNOS proteins, and TLR/NF-κB, Nrf2/HO-1, JAK/STAT, PI3K/Akt, AMPK/mTOR, VEGFA pathways.ConclusionThis study demonstrates that HSYA exerts cardioprotective effects in decreasing infarct size, reducing myocardial enzymes and improving cardiac function, which may be mediated by anti-inflammatory, antioxidant, anti-apoptotic, regulation of autophagy, improvement of microcirculation and promotion of angiogenesis. However, the absence of safety assessment, lack of animal models of co-morbidities, and inconsistency between timing of administration and clinical practice are limitations of preclinical studies.Systematic Review Registrationclinicaltrials.gov, Identifier, CRD42023460790.